The effectiveness of new hormone therapy treatments on progression-free survival of patients with HR+/HER2- metastatic breast cancer: a systematic review (Research, Society and Development, 2021)
Objective: Breast cancer is the most prevalent cancer that affects women, second only to non-melanoma skin cancers. Cyclin-dependent kinase 4 and 6 (CDK 4/6) inhibitors are the latest hormone therapy option for patients with HR+/HER2- metastatic breast cancer. Thus, the present study seeks to understand the effectiveness of new hormone therapy treatments in the progression-free survival of patients with HR+/HER2- metastatic breast cancer. Methodology: A systematic review of literature was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) model, through database searches on Pubmed, Lilacs, BioOne, The Cochrane Library, Scielo, IBECS and Medline. Results: The combination of CDK 4/6 inhibitors with aromatase inhibitors has demonstrated better results regarding progression-free survival for first-line treatment of HR+/HER2- metastatic breast cancer, being adopted by the main guidelines of American and European societies of Oncology. The best average progression-free survival was 28.2 months, achieved with the abemaciclib plus letrozole combination. As regards overall survival, the best time obtained was 54.1 months with fulvestrant monotherapy. Conclusion: CDK 4/6 inhibitors are novelty with regard to the treatment of HR+/HER2- metastatic breast cancer, having great results for progression-free survival when combined with aromatase inhibitors or fulvestrant.